Antioxidant enzymes in barley green biomass - Ehrenbergerová, Jaroslava; Březinová Belcredi, Natálie; Kopáček, Jiří; Melišová, Lucie; Smutná, Pavlína; Macuchová, Simona; Vaculová, Kateřina; Paulíčková, Ivana (Plant foods for human nutrition, 2009)
Green biomass of young barley plants exhibited statistically significant higher activity of superoxide dismutase (SOD) and catalase (CAT) at sampling I (in the phase of plant development DC 29) compared to the later sampling II (DC 31). Significant effects of varieties, years and interactions of the studied factors on the activity of the studied antioxidants were determined. During the experiment period (2005-2007), the variety Sebastian provided statistically significant higher average SOD activity (486 U.g-1) versus the variety Malz (416 U.g-1 dry matter) and line KM1910 (418 U.g-1 dry matter). No statistically significant difference was recorded between the latter two varieties. Average catalase activity of the varieties did not show any significant difference. Significantly higher CAT activity in the sampling I was recorded on average of years and locations in the variety Sebastian and hull-less line KM1910 (935 and 907 U.g-1) compared to the variety Malz (675 U.g-1). We can state that green biomass of young spring barley plants taken during the growth phase DC 29 was a significant source of enzymes catalase and superoxide dismutase in the course of the experiment (2005-2007).
Keywords: Antioxidants; výhonky rostlin; katalasa; antioxidancia; ječmen (rod); Superoxide Dismutase; Catalase; Hordeum; superoxiddismutasa; Seedlings; Plant Shoots; semenáček